Pemetaan Kajian Kepemimpinan Etis dalam Konteks Organisasi: Sebuah Scoping Literature Review (2018-2024) - Muhammad Hikam Faturrahman; Tria Raisya; Asep Irfan Asep Irfan Maulana3,; Pandu RA (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Ethical leadership is an important concept in the study of leadership and organizational behavior because it plays a role in shaping organizational values, norms, and behavior. Although research on ethical leadership continues to evolve, the existing literature shows a diversity of focuses, methodological approaches, and organizational contexts being studied. This condition causes the understanding of the direction of ethical leadership studies to become fragmented. This research aims to map the main focus of the discussion, the research approach used, and the organizational context in the study of ethical leadership through the scoping literature review approach. Data were obtained from Google Scholar using the keywords "ethical leadership" AND organization, "ethical leadership" AND organizational context, , "ethical leadership" AND organizational behavior, "ethical leadership" AND organization, and limited to publications for the period 2018-2024. Based on the systematic selection process, 14 scientific articles were obtained. The mapping results show that the study of ethical leadership is dominated by quantitative empirical research with a focus on the formation of organizational culture and climate and its influence on employee attitudes and behaviors. The organizational context studied is diverse, including the public, private, service, and social sectors. This study provides a comprehensive overview of the trends in the study of ethical leadership and identifies research gaps for further research development.